Rapidly growing sclerosing angiomatoid nodular transformation of the spleen. Issue 9 (15th September 2021) - Sohail, Amir Humza; Eze, Anthony; Sohail, Sachal; Hadi, Yousaf Bashir; Haider, Zishan; Maurer, James
Abstract: Sclerosing angiomatoid nodular transformation (SANT) of the spleen is a rare benign vascular lesion with unknown pathogenesis and no definitive pathognomonic radiological features. The majority of patients with SANT are asymptomatic, and the lesion is an incidental finding on cross-sectional imaging performed for unrelated reasons or during intra-abdominal surgery. However, in the symptomatic minority, abdominal pain is the most commonly reported symptom. SANT generally remains stable or has very slow growth, making it amenable to surveillance using serial cross-sectional imaging. Herein, we report the unusual case of SANT in a 30-year-old female with rapid growth from 6.0 × 5.6 × 4.4 cm to 8.0 × 6.6 × 7.2 cm over 21 months. Given the rapid growth, it was imperative to rule out malignancy. Thus, the patient underwent a laparoscopic total splenectomy. For SANT, splenectomy serves the dual purpose of diagnosis and definitive therapy.